1998
DOI: 10.1152/ajpregu.1998.275.5.r1412
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine modulation by PX differently affects specific acute phase proteins during sepsis in rats

Abstract: To explore the regulation of the acute phase response in vivo, the effects of pentoxifylline (PX) treatment (100 mg/kg ip 1 h before infection) were investigated in infected and pair-fed rats 2 and 6 days after an intravenous injection of live bacteria ( Escherichia coli). PX treatment prevented the increase in plasma tumor necrosis factor (TNF)-α (peak 1.5 h after the infection) and resulted in an 84 and 61% inhibition of plasma interleukin (IL)-1β and IL-6, respectively (peaks at 3 h). Plasma corticosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 42 publications
1
38
0
1
Order By: Relevance
“…The fact that IL-1 neutralization prevents IGF-I inhibition caused by LPS further strengthens this interpretation . Another possibility could be that IL-6 levels, which are less affected by pentoxifylline (Voisin et al 1998), might be able to inhibit IGF-I expression. This hypothesis is suggested by recent observations showing that IL-6 is able to inhibit basal IGF-I expression in vitro (Lelbach et al 2001) and to stimulate gene expression of SOCS-3 which exerts a negative feed-back loop controlling GH action (Ram & Waxman 1999, Colson et al 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that IL-1 neutralization prevents IGF-I inhibition caused by LPS further strengthens this interpretation . Another possibility could be that IL-6 levels, which are less affected by pentoxifylline (Voisin et al 1998), might be able to inhibit IGF-I expression. This hypothesis is suggested by recent observations showing that IL-6 is able to inhibit basal IGF-I expression in vitro (Lelbach et al 2001) and to stimulate gene expression of SOCS-3 which exerts a negative feed-back loop controlling GH action (Ram & Waxman 1999, Colson et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Pentoxifylline, a methylxanthine which is usually used in the treatment of peripheral arterial circulatory disorders, has been reported to inhibit the synthesis of TNF-in several inflammatory states, in particular in LPS-treated animals (Schade 1990, Lundblad et al 1995, Staudinger et al 1996, Voisin et al 1998. Therefore, pentoxifylline represents a useful tool for exploring the role of TNF-in the decline of IGF-I induced by LPS.…”
Section: Introductionmentioning
confidence: 99%
“…120,121 In addition, PTF shows a significant effect in modulating IFN-␥, IL-1␤, and IL-6. [122][123][124] In different models of renal disease where TNF-␣ plays a central role, such as lupus nephritis and crescentic glomerulonephritis, PTF prevents or attenuates renal injury. 125,126 Regarding diabetic nephropathy, recent experimental studies show that administration of PTF prevents an increase in renal expression, synthesis, and excretion of TNF-␣ during diabetes, which was directly and significantly associated with a reduction in renal sodium retention, renal hypertrophy, and urinary albumin excretion.…”
Section: Therapeutic Implications Of Inflammatory Cytokinesmentioning
confidence: 99%
“…11,12 Pentoxifylline (PTF) is a methylxanthine derivate and nonspecific phosphodiesterase inhibitor clinically used to treat patients with occlusive peripheral vascular disorders for more than 30 years. In addition to its rheologic properties, PTF has anti-inflammatory, antiproliferative, and antifibrotic actions [13][14][15][16][17] that have been associated with beneficial effects in experimental models of renal disease progression. 18,19 We previously reported that PTF administration to diabetic patients resulted in the reduction of clinical markers of glomerular and tubulointerstitial injury.…”
mentioning
confidence: 99%